2022
DOI: 10.1111/jcmm.17430
|View full text |Cite
|
Sign up to set email alerts
|

Combined anticancer therapy with imidazoacridinone analogue C‐1305 and paclitaxel in human lung and colon cancer xenografts—Modulation of tumour angiogenesis

Abstract: The acridanone derivative 5-dimethylaminopropylamino-8-hydroxytriazoloacrid inone (C-1305) has been described as a potent inhibitor of cancer cell growth. Its mechanism of action in in vitro conditions was attributed, among others, to its ability to bind and stabilize the microtubule network and subsequently exhibit its tumoursuppressive effects in synergy with paclitaxel (PTX). Therefore, the objective of the present study was to analyse the effects of the combined treatment of C-1305 and PTX in vivo. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Similarly, Świtalska et al describe both above-mentioned parameters for the assessment of tumor perfusion. Higher WiR values are related to more vascularized tissues and indicate higher perfusion speed [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Świtalska et al describe both above-mentioned parameters for the assessment of tumor perfusion. Higher WiR values are related to more vascularized tissues and indicate higher perfusion speed [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, sunitinib malate (Pfizer Sutent®) was identified as an oral multi‐kinase inhibitor preventing the growth, proliferation, and spread of cancers by targeting vascular endothelial growth factor receptor (VEGFR) and platelet‐derived growth factor receptor (PDGFR) (Raymond et al 2011). In our study, we identified triazoloacridone C‐1305, a microtubule stabilizing agent that also has topoisomerase II inhibitory activity, to also be a direct IRE1's RNase inhibitor (Kroliczewski et al 2020; Bartoszewska et al 2021; Switalska et al 2022). However, the wide range of other activities that many IRE1 targeting compounds have may increase the risk of off‐target effects, and thus this may limit their clinical application.…”
Section: Pharmacological Targeting Of Ire1 In Anticancer Approachesmentioning
confidence: 96%